1999
DOI: 10.1042/bj3380769
|View full text |Cite
|
Sign up to set email alerts
|

Plasmalogens as endogenous antioxidants: somatic cell mutants reveal the importance of the vinyl ether

Abstract: Exposure of plasmalogen-deficient variants of the murine cell line RAW 264.7 to short-term (0-100 min) treatment with electron transport inhibitors antimycin A or cyanide (chemical hypoxia) resulted in a more rapid loss of viability than in the parent strain. Results suggested that plasmalogen-deficient cells were more sensitive to reactive oxygen species (ROS) generated during chemical hypoxia ; the mutants could be rescued from chemical hypoxia by using the antioxidant Trolox, an α-tocopherol analogue, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(69 citation statements)
references
References 37 publications
1
67
0
1
Order By: Relevance
“…The vinyl ether bond is readily susceptible to breakdown under acidic [19,20] and oxidative conditions [7,14,21]. Since PFB hydroxylamine derivatization requires acidic conditions we tested the stability of the vinyl ether bond, the acyl ester and the amide bond under derivatization conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The vinyl ether bond is readily susceptible to breakdown under acidic [19,20] and oxidative conditions [7,14,21]. Since PFB hydroxylamine derivatization requires acidic conditions we tested the stability of the vinyl ether bond, the acyl ester and the amide bond under derivatization conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The high PLM content (15.5-35.1% of total phospholipids) in crustacean gills is thought to play a role in ion transport processes as the gill is exposed to more oxidative stress than other tissues (Chapelle and Benson, 1986). More recent studies have demonstrated the selective degradation of PLMs when lipoproteins are exposed to reactive oxygen species (Engelmann et al, 1994;Jungens, et al, 1995), and PLMs may therefore function to protect cells against reactive oxygen species by mediating the damage (Zoeller et al, 1999). Therefore, PLMs may be a component based on the environmental and physiological conditions, which could explain the distinct DMA levels obtained in fishes, crustaceans, cephalopods, gastropods and bivalves; they may be related to their different life histories.…”
Section: Dma Levels In Octopus Vulgaris and Preymentioning
confidence: 99%
“…PLMs, whose cellular functions have not been established yet (Zoeller et al, 1999), are characterised by the presence of an aldehydic chain attached to a glycerol backbone through a vinyl ether (alkenyl) linkage (Malins and Varanasi, 1972;Horrocks and Sharma, 1980) and by a higher content of polyunsaturated fatty acids (PUFAs) than 1-alkyl-2-acyl and diacyl forms (Dembitsky, 1988). Their presence has been shown in a number of marine organisms (Rapport and Alonzo, 1960;Dembitsky, 1979;Sargent, 1989;Jeong et al, 1999;Kikuchi et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Plasmalogens (PIs), a subclass of glycerophospholipids possessing a vinyl-ether bond at the sn-1 position, are biosynthesized and regulated in peroxisomes [4][5][6]. Therefore, plasma Pls may reflect the systemic functional state of peroxisomes, and serve as potential biomarkers for diseases related to oxidative stress and aging [7][8][9]. Human plasma Pls are synthesized mainly in the liver and secreted into the blood as lipoprotein components.…”
Section: Introductionmentioning
confidence: 99%